Text memorization: An effective strategy to improve Chinese EFL learners’ argumentative writing proficiency - Wang, Qunfeng (Frontiers in Psychology, 2023)
This study aims to explore the impact of text memorization strategies on Chinese EFL learners’ English argumentative writing proficiency, the process of their text memorization, and specific strategies deployed for the enhancement of the memorization effect. Seven text memorization tests, one pre-test, and one post-test were administrated to 33 Chinese English majors to, respectively, examine students’ memorization outcomes as well as their English argumentative writing proficiency before and after memorizing seven model English writings. Data were also collected through interviews with the 12 top scorers in text memorization tests. The results showed that text memorization as a foreign language learning strategy significantly impacted the improvement of EFL learners’ argumentative writing proficiency. Moreover, in the text memorization process, in which varieties of strategies were employed, it was found that storage was preceded by understanding among the majority of the interviewees. Since text memorization was found to be advantageous to EFL learners’ writing proficiency, a new system of text memorization strategies was developed in the current study to provide both scholars and teachers with insight into text memorization strategies associated with the writing skills of EFL learners.